1992
DOI: 10.1038/sc.1992.152
|View full text |Cite
|
Sign up to set email alerts
|

Physeal injuries in myelomeningocele patients

Abstract: Epiphysiolysis from a series of 253 patients under regular control in the Spina Bifida Unit at our hospital has been analysed from 1967 to the present time. From that total there have been 18 physeal fractures in 9 of the myelomening ocele patients. The clinical characteristics, diagnostic difficulties and therapeutic criteria for this type of lesion are considered, and we suggest the need to use suitable orthoses whenever the patient is able to walk, and to temporarily increase the level of orthotisation in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(6 reference statements)
1
8
0
Order By: Relevance
“…In the literature, figures ranging from 4% to 9% have been reported [8, 9, 27]. The relatively good walking ability of patients who suffered epiphyseal fractures is in line with observations made by Kumar et al.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the literature, figures ranging from 4% to 9% have been reported [8, 9, 27]. The relatively good walking ability of patients who suffered epiphyseal fractures is in line with observations made by Kumar et al.…”
Section: Discussionsupporting
confidence: 82%
“…Epiphyseal fractures occur frequently in patients with MMC at rates of 4–9% [8, 9, 28] and can affect further bone growth. In contrast to other kinds of fractures, epiphyseal injuries mainly seem to affect those MMC children who can walk relatively well [24, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Roberts et al [99] suggested that repetitive microtrauma in non-sensitive limbs could produce micromovements in the zone of transformation of the cartilage, compromise the calcification process, and lead to the widening of the proximal non-calcified portion of the physis [99]. Failure to use orthoses for walking in patients requiring these aids constitutes a risk factor with regard to epiphysiolysis [100,101]. Kumar et al [21] reported that epiphyseal fractures occur most often in patients in a low lumbar ambulatory group, but they can occur at any level of motor paraplegia [21,101].…”
Section: Site Of Fracturementioning
confidence: 99%
“…Failure to use orthoses for walking in patients requiring these aids constitutes a risk factor with regard to epiphysiolysis [100,101]. Kumar et al [21] reported that epiphyseal fractures occur most often in patients in a low lumbar ambulatory group, but they can occur at any level of motor paraplegia [21,101]. James showed that due to the fragility of the bone, the insertions of the gastrocnemius and of the hamstrings around the knee may cause the displacement of the epiphyses when these mus-cles are spastic and the knee joint is repeatedly forced straight, as occurs during the application of splints [5].…”
Section: Site Of Fracturementioning
confidence: 99%
“…Copyright © Elisa López-Dolado OPROJ.000673. 7 (5).2020 but possibly be found a history of minor trauma [5], while physeal fractures are usually associated with repeated forces of stress that are thought to impact this growing part of the bone during walking [5,6], with no history of trauma maybe because of not wearing a suitable orthosis. Taking into account the lack of sensibility due the injury, these patients will not present pain and the only symptoms which may appear are swelling, local redness, local hyperthermia and sometimes high leukocyte count and high temperature, being the last two symptoms specially observed in case of metaphyseal and diaphyseal fractures, which can simulate an osteomyelitis or sarcoma [7][8][9].…”
Section: Introductionmentioning
confidence: 99%